Language Planning Policy and its Impact on Literary Theory and Cultural Studies - Yadav, Aditya Kumar (Journal of Advanced Research in English & Education, 2023)
Language planning policies play a pivotal role in shaping the linguistic, literary, and cultural landscape of societies worldwide. This comprehensive review article delves into the complex interplay between language planning policy and its profound influence on literary theory and cultural studies. We explore how language policies can have far-reaching effects on the development and preservation of cultural identities, as well as the creation and interpretation of literature. This article delves into the implications of language choice, linguistic inclusivity, and language revitalization efforts on these fields, drawing examples from diverse regions and contexts. By examining the symbiotic relationship between language planning policies, literary theory, and cultural studies, this article offers a comprehensive overview of the multifaceted connections between language and culture.